Inducible Displacement of Cementless Femoral and Tibial Components Throughout Weight-bearing Flexion - Hext, Rebecca A.; Broberg, Jordan S.; Howard, James L.; Lanting, Brent A.; Teeter, Matthew G. (Arthroplasty today, 2025)
Cementless fixation for total knee arthroplasty has been increasing following advancements in implant designs. The use of cementless designs has been supported through longitudinal radiostereometric analysis (RSA) studies; however, few studies have used inducible displacement exams to assess fixation throughout flexion. Our primary aim was to assess patterns and locations of inducible displacement throughout flexion. Participants (n = 24) received a fixed-bearing, cruciate-retaining cementless implant. At 1-year postoperation, participants underwent a supine RSA exam and standing RSA exams at 0°, 20°, 40°, and 60° of knee flexion. Inducible displacements were reported as maximum total point motion and as 3-dimensional translations at points of interest. Inducible displacement of the tibial component increased with knee flexion angle and was 1.129 ± 0.644 mm at 0°, 1.181 ± 0.462 mm at 20°, 1.526 ± 0.386 mm at 40°, and 1.648 ± 0.461 mm at 60°. Inducible displacement of the femoral component increased with knee flexion angle and was 0.704 ± 0.364 mm at 0°, 0.839 ± 0.458 mm at 20°, 1.011 ± 0.451 mm at 40°, and 1.203 ± 0.708 mm at 60°. The strongest correlations between 3-dimensional translation and knee flexion angle were at the stem tip for the tibial component, and anterior flange tip for the femoral component. Inducible displacement measurements increased with knee flexion angle. At 0°, both components had values consistent with well-fixed components. The locations of maximal displacements support these components are well-fixed and demonstrate that inducible displacement throughout flexion is due to mechanical loading.